PENERAPAN MODEL PROBLEM BASED LEARNING MELALUI MEDIA DIGITAL INTERAKTIF SCRAMBLE DALAM MENINGKATKAN HASIL BELAJAR PADA PEMBELAJARAN BAHASA INDONESIA SISWA KELAS V SDN BANJARSAWAH I - Dwi Ryanti; Ribut Sriwijayanti; Ludfi Arya Wardana (STKIP Subang, 2026)
This research was motivated by the low learning outcomes of fifth-grade students in Indonesian language learning at SDN Banjarsawah I. The problem was caused by teacher-centered learning, monotonous lecture model, and the lack of student involvement in the learning process. These conditions made students less active, less focused, and many of them had not achieved the Minimum Completeness Criteria (KKM) 75%. Therefore, an innovative learning model and media were needed to create an active, interesting, and enjoyable learning atmosphere. One alternative applied in this research was the Problem Based Learning (PBL) model through Interactive Digital Scramble Media. This study aimed to determine the implementation of the Problem Based Learning model through Interactive Digital Scramble Media and to identify the improvement of students’ Indonesian language learning outcomes after the implementation of the model. This research used Classroom Action Research (CAR) based on the Kemmis and McTaggart model, which consists of planning, action, observation, and reflection stages. The study employed qualitative and quantitative approaches and was conducted in two cycles. The results showed that the implementation of the Problem Based Learning model through Interactive Digital Scramble Media improved students’ learning outcomes in Indonesian language learning. The improvement was indicated by better understanding of learning materials, improved ability to answer questions, enhanced task completion skills, increased participation in discussions, higher learning motivation, and greater confidence in expressing opinions. The percentage of students’ learning mastery improved in each cycle, from 50% in the pre-cycle, to 70% in Cycle I, and reached 100% in Cycle II. Therefore, the implementation of the Problem Based Learning model through Interactive Digital Scramble Media proved to be effective in improving Indonesian language learning outcomes of fifth-grade students at SDN Banjarsawah I